Fisioterapia respiratória, pressão intra-abdominal e função renal de pacientes de terapia intensiva - Demarchi, Ana Carolina dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Rationale: The presence of Abdominal Hypertension is a frequent condition in ICU patients with a significant impact on mortality. Critical patients have several risk factors for increased abdominal pressure, including mechanical ventilation and positive water balance. A slight increase in abdominal pressure can lead to organ dysfunction, including the Acute Renal Injury, which is a prevalent complication affecting patient in intensive care with a significant impact on mortality. Patients submitted mechanical ventilation are daily undergoing respiratory therapy techniques, however there aren’t studies demonstrating the effects of the techniques used in intensive care on intra-abdominal pressure and renal function in these patients. Objective: To evaluate the influence of different techniques of respiratory physiotherapy on intra-abdominal pressure on critical patients as well as the behavior of renal function and abdominal hemodynamic by implementing these techniques. Patients and Methods: Clinical trial conducted randomized, controlled, crossover, from March 2013 to December 2014 in the Intensive Care Unit at Hospital of São Paulo State University (UNESP-HC) (Botucatu, Brazil). Patients were randomized to receive three sequences of techniques that included: Chest Compression Expiratory, Hyperinflation and Manual Bag-Squeezing. All patients were submitted to three techniques in different consecutive days. Analysis of the technical data were grouped according to the measures carried out and compared among each other. Hemodynamic parameters were evaluated and intra-abdominal pressure before, after and within two hours after the intervention. Renal function was assessed by creatinine clearance, urea clearance and sodium excretion fraction and the intra-abdominal pressure assessed by the original method of Kron at the same moments. Results: We evaluated 31 patients, 17 males with a mean age of 58.1 ± 17.6 years. Intra-abdominal pressure decreased in a statistically significant way with the use of three techniques and two different times that were evaluated. Immediately after the Manual Hyperinflation technique there was a statistically significant increase in glomerular filtration gradient and the Bag-Squeezing technique, there was also an increase in glomerular filtration gradient immediately after and in two hours of intervention. There was an increase of abdominal perfusion pressure immediately at the end and two hours after application of this technique. The urea clearance showed an increase after the implementation of the Bag-Squeezing technique and increased sodium excretion fraction to the technical Manual Hyperinflation and Bag-Squeezing also were observed. Conclusions: Respiratory therapy techniques reduced pressure and improved intra-abdominal hemodynamic in critical care patients. Technical Manual Hyperinflation and Bag-Squeezing increased sodium excretion fraction, and only the last technique increase the clearance of urea. In general, the techniques employed were associated with improvement of the evaluated parameters.

Fundamentação. A presença de Hipertensão Abdominal é condição frequente em pacientes de UTI com importante impacto sobre a mortalidade. Tais pacientes contam com diversos fatores de risco para aumento da pressão abdominal, entre eles ventilação mecânica e balanço hídrico positivo. Um discreto aumento da pressão abdominal pode levar a disfunções orgânicas, entre elas a Lesão Renal Aguda, complicação bastante prevalente, que acomete pacientes internados em terapia intensiva, com importante impacto sobre a mortalidade. Pacientes de terapia intensiva e em ventilação mecânica são diariamente submetidos a técnicas de fisioterapia respiratória, entretanto não foram localizados estudos que demonstrassem os efeitos das técnicas mais utilizadas em terapia intensiva sobre a pressão intra-abdominal e função renal destes pacientes. Objetivos. Avaliar a influência de diferentes técnicas de fisioterapia respiratória sobre a pressão intra-abdominal de pacientes de terapia intensiva, bem como o comportamento da função renal e hemodinâmica abdominal com a aplicação destas técnicas. Casuística e Método. Foi realizado ensaio clínico, randomizado, controlado, cruzado, no período de março de 2013 a dezembro de 2014, no Serviço de Terapia Intensiva da Faculdade de Medicina de Botucatu-SP. Os pacientes foram randomizados para receberem três possíveis sequências de técnicas que incluíam: Compressão Torácica Expiratória, Hiperinsuflação Manual e Bag-Squeezing. Todos os pacientes foram submetidos às três técnicas, em dias diferentes e consecutivos. Para análise das técnicas os dados foram reagrupados de acordo com as intervenções realizadas e comparados entre si. Foram avaliados parâmetros hemodinâmicos e pressão intra-abdominal antes, após e nas duas horas seguintes às intervenções. A função renal foi avaliada por meio do clearance de creatinina, clearance de uréia e fração de excreção de sódio e a pressão intra-abdominal avaliada pelo método original de Kron nos mesmos momentos. Resultados. Foram avaliados 31 pacientes, 17 do gênero masculino com idade média de 58,1 ±17,6 anos. A Pressão intra-abdominal diminuiu de forma estatisticamente significante com a utilização das três técnicas e nos dois momentos em que foram avaliadas. Imediatamente após a técnica Hiperinsuflação Manual, houve aumento estatisticamente significante do gradiente de filtração glomerular e com a técnica Bag-Squeezing, observou-se aumento do gradiente de filtração glomerular imediatamente após e nas duas horas seguintes à intervenção. Foi observado aumento da pressão de perfusão abdominal imediatamente após e nas duas horas seguintes à aplicação da referida técnica. O clearance de uréia apresentou aumento após a aplicação da técnica Bag-Squeezing e também foi observado aumento da fração de excreção de sódio com as técnicas Hiperinsuflação Manual e Bag-Squeezing. Conclusões. Técnicas de fisioterapia respiratória reduziram a pressão e melhoraram a hemodinâmica intra-abdominais de pacientes de terapia intensiva. As técnicas Hiperinsuflação Manual e Bag-Squeezing aumentaram a fração de excreção de sódio e apenas a última o clearance de uréia. De maneira geral, as técnicas empregadas se associaram a melhora dos parâmetros de avaliados.
Respiratory physiotherapy, intra-abdominal pressure and renal function intensive care patients
Keywords: Intra-abdominal pressure; Renal function; Respiratory physiotherapy; Intensive therapy; Modalities of respiratory therapy; Pressão intra-abdominal; Função renal; Fisioterapia respiratória; Terapia intensiva; Modalidades de fisioterapia respiratória